Spatial distribution of pipe collapses in Goodwin Creek Watershed, Mississippi. Issue 14 (23rd May 2012) - Zhang, T.; Wilson, G. V.
Abstract The internal erosion of soil pipes can induce pipe collapses that affect soil erosion processes and landform evolution. The objective of this study was to determine the spatial distribution of pipe collapses in agricultural fields of Goodwin Creek watershed. Ground survey was carried out to detect pipe collapses, and the location, size and surface elevation was measured with differential GPS. A total of 143 of the 145 pipe collapses were found in cropland, and the density was approximately 0.58 collapses per hectare. The spatial distribution of pipe collapses was not uniform as pipe collapses were concentrated in the flat alluvial plains where the land use was dominated by cropland. One of the four parcels had 90% of the pipe collapses with a density of 7.7 collapses per hectare. The mean depth, area and volume of these pipe collapses were 0.12 m, 0.34 m2 and 0.02 m3, respectively, and all these properties exhibited a skewed distribution. The drainage area–slope gradient equation, which has been widely used for erosion phenomenon prediction, did not represent pipe collapses in this study as the coefficient of determination was <0.01. This is clear evidence that subsurface flow is not represented by surface topographic characteristics. The pipe collapses were found to intercept runoff, thereby reducing the slope length factor by 6% and the drainage area by 7%. Both of these factors can reduce the sheet and rill erosion; however, the increased subsurface flow could enhance ephemeral gully erosion. Published 2012. This article is a U.S. Government work and is in the public domain in the USA.